Effect of Public Service Quality on People Satisfaction toward Implementation of Integrated Administration Service Kecamatan in New Normal Era Kecamatan Sako Palembang City - Austin, Trecy; Hestiriniah, Deby Chintia (FIA UB, 2021)
2020 is the year of the COVID-19 pandemic which made Government implement Large Scale Social Restriction Policy, both Social Distancing and Physical Distancing. However, based on the observation results made by the researcher in the field of the PATEN process in Kecamatan Sako during new normal, people were not yet discipline in dealing with online services. The services continue as usual by implementing strict health protocol such as to wash hands with soap often, to wear mask, to maintain a distance of a meter. Based on the survey conducted in Kecamatan Sako, the respondents still did stuff on the spot directly because the physical files still had to be collected at the PATEN counter to be processed. According to a direct interview conducted with the Head of the Government Section, the management of Family Card and ID card was carried out at the UPT Zone VIII of civil registration since April 23, 2020. The purposes of this study are to analyze the effect of service quality (tangibles, reliability, responsiveness, assurance, and empathy) on people satisfaction in Kecamatan Sako and to explain the dimensions of service quality (tangibles, reliability, responsiveness, assurance, and empathy), which dimensions have the most dominant influence on people satisfaction in Kecamatan Sako. This study uses quantitative methods. The method used in data collection is Proportionate Random Sampling. The data quality test consists of testing the validity and reliability of the data using multiple linear regression. The results of this study indicate that the t value is 1.985 with a significant value of 0.015 <0.05, so that the results of the first problem formulation are Tangible, Assurance, and Empathy which have a significant effect on the variable of people satisfaction. The second problem formulation explains that the empathy variable is the variable that has the most dominant influence on the dependent variable or dependent (y) with the largest Beta value which is 0.551.